Integrating Smart Technologies in Horticulture: Drivers, Challenges, and Strategies for Sustainable Management (International Journal of Food and Nutritional Sciences, 2022)
Through smart technologies, traditional agricultural practices are being transformed toward higher levels of productivity, efficiency, and sustainability. Advanced tools like the Internet of Things, artificial intelligence, robotics, and precision farming help in soil and weather monitoring as well as crop health in real time. Resource optimization is achieved by reducing the level of water consumption as well as lessened application of chemicals and improving quality yield. Through big data analytics, machine learning would further help farm owners make optimal decisions, having better crop managements and adapting to environmental unpredictability. But the integration of smart technologies for horticultural purposes is seriously challenged by an expensive implementation fee, technical intensity, and ignorance of digitalized literacy among growers. Infrastructure shortages, such as internet connectivity availability and power source in rural towns, also face a challenge from the adoption phase. Moreover, the concern of data privacy, cybersecurity, and reliance on technology presents crucial ethical and operational issues. In this context, government policies, financial incentives, and training programs are going to be pivotal in overcoming the hurdles and promoting accessible smart agriculture solutions. This will be achieved with strategic approaches targeted at bridging the technological gap through farmer education and research collaborations, along with scalable innovation for smart farming solutions. Public-private partnerships will help in infrastructure development and financial support, thereby making smart farming solutions more accessible. Policy frameworks that promote sustainable practices, environment protection, and climateresilient technologies will be necessary for long-term agricultural transformation. By effectively utilizing smart technologies, horticulture can move forward towards greater sustainability, improved food security, and economic growth while mitigating environmental impacts.